2015
DOI: 10.1007/s10384-015-0388-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of corneal irregular astigmatism on visual acuity after conventional and femtosecond laser-assisted Descemet’s stripping automated endothelial keratoplasty

Abstract: Visual outcomes after f-DSAEK were poor compared to conventional m-DSAEK due to an increase in irregular astigmatism caused by posterior surface irregularities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…We demonstrated that HOAs caused by a graft fold in the posterior surface degraded visual acuity after DSAEK. 47 The effect of folds in the posterior surface is not negligible for postoperative visual acuity. We sometimes find graft folds just after the insertion of the DSAEK graft into the anterior chamber.…”
Section: From Theory To Clinical Applicationmentioning
confidence: 99%
“…We demonstrated that HOAs caused by a graft fold in the posterior surface degraded visual acuity after DSAEK. 47 The effect of folds in the posterior surface is not negligible for postoperative visual acuity. We sometimes find graft folds just after the insertion of the DSAEK graft into the anterior chamber.…”
Section: From Theory To Clinical Applicationmentioning
confidence: 99%
“…The use of microkeratome in DSAEK procedure is beneficial in terms of decreased astigmatism, rapid visual recovery, and reduced rejection rate. [ 92 ] In a post-DSAEK cornea, the posterior surface of the cornea is not parallel to the anterior surface of the DSAEK donor tissue. This leads to increase in the higher order aberrations of up to 25%.…”
Section: Descemet's Stripping Endothelial Keratoplastymentioning
confidence: 99%
“…The irregular posterior corneal surfaces are supposed to result in an increase in total HOAs and degraded quality of vision. [ 16 ] However, to the best of our knowledge, the influence of HOAs on visual acuity is still poorly understood in eyes with corneal dystrophies. In the following study, we hypothesized that increased HOAs have adverse effects on the visual acuity in corneal dystrophies, although the reason for decreased visual acuity in these corneal dystrophies have been thought to be due to the stromal opacities.…”
Section: Introductionmentioning
confidence: 99%